Hurdles to international terrorist alliances: lessons from Al Qaeda’s experience - Bacon, Tricia (Terrorism and political violence, 2017)
Despite the threat posed by international terrorist alliances, the conditions that foster and inhibit these relationships remain poorly understood. When seeking allies outside of their primary conflict and political market, groups struggle to forge credible commitments, particularly the requisite ‘shadows of the future’ and reputations conducive to cooperation, without third-party enforcers. Given their suspicious nature and strong in-group identities, terrorist groups sometimes balk at relinquishing independence for security. Alliances risk precipitating counterterrorism pressure, alienating constituents, and increasing the risk of betrayal. Even groups that enjoy alliance success, like Al Qaeda, experience these hurdles in their alliance. What helped to set Al Qaeda apart from most groups was its ability to navigate these obstacles, though some bedeviled its alliances efforts. This offers under-utilized opportunities for alliance disruption.